2022
DOI: 10.1210/clinem/dgac021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Doses of Exercise on Inflammation Markers Among Adolescents With Overweight/Obesity: HEPAFIT Study

Abstract: Propose Obesity-related metabolic risk factors in adolescents with overweight/obesity may be associated with systemic low-grade inflammation, and therefore we investigated whether a 6-month exercise training altered markers of inflammation. Methods Secondary analyses of a randomized controlled exercise-based intervention trial (September 2017 to December 2018). Adolescents aged 11 to 17 years (Tanner stage II to V), 70% girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(42 reference statements)
0
5
0
1
Order By: Relevance
“…We first imported the documents into the document management software Endnote, and after removing duplicate documents and screening titles and Ramirez-Velez etal. 30 1…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first imported the documents into the document management software Endnote, and after removing duplicate documents and screening titles and Ramirez-Velez etal. 30 1…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Each exercise lasts 60 min, with walking and running at different intensities crossed Tadiotto et al 28 HIIT reduces BMI-z, waist-to-height ratio, and improves physical fitness 52 adolescents (11)(12)(13)(14)(15)(16) Ramirez-Velez etal. 30 Based on the LIPE and groups, several levels of circulating inflammation can be significantly altered 95 adolescents (M = 13.5 ± 1.6 years) Randomly assigned School-based exercise programs. 3 times a week for 6 months Cao et al 31 HIIT was highly effective in improving cardiopulmonary function fitness compared to MICT and had a similar effect in improving body composition in obese boys.…”
Section: Randomly Assigned Cycling Interventions Of Varying Intensitymentioning
confidence: 99%
“…A clinical study (NCT02753231) shows that a low-to-moderate intensity physical education class (LIPE), or its combination with a high-intensity physical education class, significantly regulates the expression of inflammatory or immune regulatory markers, including C-X-C motif chemokine ligand 13 (CXCL13, or BLC), C-C motif chemokine ligand 5 (CCL5), CCL11, CCL13, CCL18, and FGF6 [ 74 ]. A mouse study also shows that exercise reduces the expression of TNF-α and macrophage marker F4/80 in adipose tissues in HFD-fed mice, but it increases the expression of the M2 macrophage marker CD163, indicating phenotypic switching from M1 to M2 macrophages in adipose tissues [ 75 ].…”
Section: Molecular Targets For Obesity Treatmentmentioning
confidence: 99%
“…In addition to these single comparisons of uni – and multi‐modal aerobic and RE protocols, a systematic review revealed that aerobic exercise (AE) is more likely than other types to induce a negative impact on the TLR4 pathway (Cavalcante et al, 2017). In addition, a cytokine antibody array (more than 60 biomarkers) study comparing the effects of four different exercise modalities on inflammation revealed that combined exercise (multi‐modal) is more likely to reduce chronic systemic low‐grade inflammation during obesity (Ramírez‐Vélez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%